Alcohol Provoked Father-Son Assault: A Case Report from Nepal - Atreya, Alok; Nepal, Samata; KC, Arjun (Birat Journal of Health Sciences, 2020)
Although a causal relationship between alcohol and violence is established, the actual number of alcohol related violence are seldom reported. Consumption of alcohol is part of ritual or ceremony in indigenous communities in Nepal. However, alcohol related domestic violence are rarity in Nepalese scenario. This may be because alcohol related domestic assaults and violence are usually ’secreted’ and seldom published. We present a case of father-son alcohol related aggression for its unusualness of site and pattern.